How is multi-criteria decision analysis supporting existing software for nature-based solutions decisions? - Mozumdar, Shreya; Cinelli, Marco (Frontiers in Sustainability, 2026)
IntroductionNature-based solutions (NbS) involve working with and enhancing nature to address social challenges, aiming to protect, manage and restore natural ecosystems. While recognition of their benefits and cost-effectiveness is improving, there remain challenges to their adoption. Since they are often multi-stakeholder problems and aim to achieve multiple objectives, Multiple Criteria Decision Analysis (MCDA) is a good methodology to assist with their planning and implementation. In addition, software tools that support the MCDA process while evaluating NbS help manage varying stakeholder preferences and facilitate collaboration between them. They also make complex information about NbS problems easier to visualise, express and interpret. Current analyses of NbS either do not focus on MCDA or when they do, they do not examine how software can support the implementation of MCDA in evaluating NbS.MethodsThis study thus conducted a systematic literature review via Web of Science and Google Scholar to analyse a sample of software that assess NbS using methods that support any part of the MCDA process. We analysed the technical aspects of the software, their scope of analysis and their capability to support complex decision-making for NbS selection, implementation and management.Results and discussionWe found that the software assess a wide variety of scopes and often include a spatial GIS component too. They cater to different users, among which are public officials, private-sector businesses and consultants. They mainly assist with the planning and design of NbS, rather than their management. The software assess many different co-benefits of NbS—the most common ones being hydrology, carbon uptake, air quality and socio-economic factors. By suggesting NbS alternatives and describing their performance, they also support decisions by making NbS benefits more understandable and streamlined to decision-makers. Most of the software only allow the assessment of one alternative at a time, rather than supporting the comparison of multiple NbS. Software developers should justify and align their weighting and aggregation methods in documentation and should broaden the scope of their software's analysis in the future to include biodiversity, non-urban NbS and enhancement of stakeholder engagement and cooperation during the whole MCDA process, from problem formulation to provision of a decision recommendation.